LENGTH-WEIGHT RELATIONSHIP IN THE CAT-FISH, TACHYSURUS THALASSINUS (RUPPELL) - Mojumder, P (Indian Journal of Fisheries, 2011)
The length-weight relationship in Tachysurus thalassiuus has been worked out.There was no significant difference between the relationships in males and females andhence ,3 common equation for both the sexes has been arrived at.